Manual de buenas prácticas de manufactura para la inocuidad de la producción de cerveza en la microempresa “JAGOBREWER” - Loor Guadamud, Jordan José (2022)
Good Manufacturing Practices are essential instruments that fulfill the purpose of obtaining safe products suitable for human consumption, so the objective of this research was to design a manual of Good Manufacturing Practices for the safety of beer production in the microenterprise "Jagobrewer". The starting point was a review of the literature that supports our GMP problem. The techniques used were the checklist and the interview, which were used in the initial diagnostic phase according to the Resolution of ARCSA-DE-042-2015-GGG, with respect to the requirements established in the standard for work areas, equipment and machinery, materials, obligations of operators, raw materials and inputs, production process, packaging, labeling, transportation, marketing, quality assurance and control. The descriptive statistical method was used to establish the levels of compliance with GMP; the results showed an average score of 2.22 for raw materials, very close to high, and 3.32 for personnel obligations, very close to low. Once these results were validated, a plan of activities was drawn up to help the microenterprise take measures for beer production, and a Good Manufacturing Practices Manual was designed. The application of these practices as a methodology for improving the production process in the "Jagobrewer" company will contribute to guaranteeing the quality and safety of the product.